From Generation to Generation - Donald E. Abelson (International Review of Public Policy)
This study offers a series of reflections on the evolution of think tanks in Europe and the United States. In addition to exploring how these organizations have come to place a higher premium on political advocacy than rigorous policy research, the article raises a series of questions about how the preoccupation of think tanks with their global rankings, and their desire to inundate stakeholders with quick response policy research, can have serious implications for how policymakers formulate public policy. In the end, this study argues that for think tanks to serve the public interest, they need to engage in scientific research that adheres to proper and verifiable academic standards. Otherwise, these organizations will join the growing chorus of voices whose only interest is to serve their own institutional goals and those of their benefactors.